INHIBITORY EFFECT OF A STANDARDIZED HYDROETHANOLIC EXTRACT OF TERMINALIA ARJUNA BARK ON ALPHA-AMYLASE ENZYMEINHIBITORY EFFECT OF A STANDARDIZED HYDROETHANOLIC EXTRACT OF TERMINALIA ARJUNA BARK ON ALPHA-AMYLASE ENZYME - Shengule, Sushant A; Mishra, Sanjay; Bodhale, Shweta (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The present study was initiated to screen the hydroethanolic bark extract for Î±-amylase inhibitory activity and standardization of the Terminalia arjuna for polyphenolic phytochemicals using high-performance liquid chromatography-photo diode array (HPLC-PDA) method. Methods: The T. arjuna bark sample was extracted with ethanol: water (70:30 v/v) using Soxhlet extraction. A Dionex P680 HPLC system was used to acquire chromatograms. The screening of extract of T. arjuna bark has performed for in vitro Î±-amylase inhibitory assay. Each experiment was repeated 3 times. All values were expressed mean Â± standard deviation. Results: The content of arjunetin, arjungenin, gallic acid, ellagic acid, and quercetin was 0.47, 8.22, 2.443, 7.901, and 3.20 mg/g, respectively, in a hydroethanolic extract of T. arjuna. The hydroethanolic extract of T. arjuna bark and acarbose has shown an inhibitory activity with an IC50 value 145.90 and 62.35 Î¼g/mL, respectively. Conclusion: The hydroethanolic extract T. arjuna bark demonstrates Î±-amylase inhibitory activity due to a synergistic effect of the phytochemical constituents present in it. This study suggests that one of the mechanisms of this plant for antidiabetic activity is through the inhibition of Î±-amylase enzyme.